2019
DOI: 10.1108/tlo-02-2019-221
|View full text |Cite
|
Sign up to set email alerts
|

Organizational learning in stakeholder relations

Abstract: Purpose The purpose of this paper is to highlight the challenges regarding learning in stakeholder relations in profit and nonprofit organizations. Design/methodology/approach Conclusions and models presented in the paper have been designed based on the systems perspective, critical thinking and critical review of previous contributions. Findings Organizational learning has been examined in profit and nonprofit organizations, and factors which stimulate this process have been identified. More precisely, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Another study found that the sub-factors of "commitment to learning," "a shared vision," and "intra-organizational knowledge sharing" are conclusively related to the OL concept in innovation (Kiziloglu, 2015). In Rupcic's (2019) view, OL is a significant factor in higher education institutions, in the learning dynamics in university-industry collaborations, and in inter-professional learning.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Another study found that the sub-factors of "commitment to learning," "a shared vision," and "intra-organizational knowledge sharing" are conclusively related to the OL concept in innovation (Kiziloglu, 2015). In Rupcic's (2019) view, OL is a significant factor in higher education institutions, in the learning dynamics in university-industry collaborations, and in inter-professional learning.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…On the other hand, Fernandez and Thams (2019) theorized shared co-working experience could increase trust and team cohesiveness, which when combined with diversity in national origin, race, gender and ethnicity could lead to diversity of skills, knowledge and mental models. And the outcome of diverse stakeholder learning networks would be a more vivacious learning environment and a more balanced strategic management of stakeholders (Rupcic, 2019). Consequently, the second hypotheses are made as follows:…”
Section: Stakeholder Networkmentioning
confidence: 99%
“…In the current challenging business environment, intangible assets, such as learning capability, human capital, knowledge management and relationships with stakeholders are now the major sources of competitive advantage (Mubarik et al , 2016; Haskel and Westlake, 2017; Jones et al , 2018; Rupcic, 2019). The growing importance of intangible assets has opened up many new areas of research in the last few decades.…”
Section: Introductionmentioning
confidence: 99%